Signifikansi Pembelajaran Inkuiri Dengan Konsep Ehipassiko Dalam Pendidikan Buddhis - Asa Murti Suryaning Ratri; Widiyono Widiyono; Hastho Bramantyo (Jurnal Maitreyawira, 2024)
Education is a process of developing reasoning power, skills, and morality to develop the potential of every human being. Education makes a very big contribution to the progress of a nation. The efforts to improve education in Indonesia are by moving all the components that make up a quality system in education. The research used in this study is library research or library research, namely research conducted by collecting data or scientific writings that aim to be research objects or data collection that is of a literary nature. The discussion in this study was carried out using the checklist or synthesize checklist method which was derived from text, context, and discourse. The inquiry learning model with the ehipassiko concept has not been implemented yet because there is still a lack of understanding of how these two concepts work. Even though these two concepts have a lot in common, it is still very difficult to do because it requires proper understanding and strategies that are in accordance with these two concepts. So that the collaboration or combination of these two teaching models will be successful.